Per un Medioevo plurale: Global Middle Ages e Federico II (Doctor Virtualis, 2021)
The topic we intend to develop in this essay is the relationship between narration and historical (re)construction. We will examine the meaning behind the current concept of narrative in historiography, with a dialectical approach towards the paradigm of global Middle Ages, an expression firstly used by historians Catherine Holmes and Naomi Standen in 2018. To perform an in depth analysis of the abovementioned relationship, we will use as a case study the figure of Frederick II. A significant emphasis will be put on the biographical construction and myths, especially in the relationship with other cultures. The aim of our essay is to provide a framework within it would be easier to overcome the two traditional macro interpretations of Middle Ages, studied by Tommaso di Carpegna Falconieri and David Matthews: Middle Ages as a backward reign of darkness and Middle Ages as the morning light, at the origin of many contemporary political identities – not least that of the European Union.